A realist assessment of the implementation of blended learning in a South African higher education context - Abrahams, M A; Witbooi, S (South African Journal of Higher Education, 2016)
Opportunities for further studies by working adults came under threat as the University of the Western Cape stopped the offering of after-hours classes in most of its Faculties. Unqualified and under-qualified librarians were directly affected by this decision. This paper outlines an assessment of the conceptualisation and implementation of an action research project initiated by the Division for Lifelong learning. Using a realist evaluation approach, the assessment focuses on the implementation of strategies aimed at showing how lifelong learning opportunities, conceptualised and provided in flexible ways, could support innovation in learning and teaching in order to enhance access and success to learning by working people in the context of the Library and Information Science Department.